Впровадження елементів системи менеджменту якості в науковій бібліотеці ХНУРЕ - Бояріна, Л. О. (Weber, 2010)
Modern management quality system for library is a total quality management one. Here we used the process approach to implement in the scientific library work. In scientific library of Kharkiv nationality university of radioelecrtonics was chosen the creation process of electronics’ documents. The technological map was designed to this department. Based on such maps we can selected processed need to improvement.
Keywords: елементи системи менеджменту